Designing high efficiency graphite felt electrode via HNO3 vapor activation towards stable vanadium redox flow battery. (1st February 2023) - Wu, Xuewen; Xie, Zhiyong; Zhou, Haikun; Xiong, Zi'ang; Yin, Xingrong; Tang, Hongli; Ma, Qiang; Liao, Jingjing
Highlights: Steaming via nitric acid vapor treated graphite felts for VRFB application. It is a low cost, low energy consumption process, allowing large scalability and precise control method. A sequence reaction mechanism is proposed for the nitric acid vapor treated graphite felt reactions occurring at 200°C. The m-GF-0.45 electrode displays excellent electrocatalysis toward the VO 2+ /VO2 + and V 2+ /V 3+ redox couples in VRFBs. Abstract: A new method of preparing nitric acid vapor treated graphite felt for vanadium redox flow battery (VRFB) is developed. This method outperforms traditional impregnation methods in convenience, efficacy and controllability of fabrication process. A sequence reaction mechanism is proposed for nitric acid vapor treated graphite felt reactions occurring at 200 °C. The modified-graphite felt (m-GF) with excellent electrocatalytic redox reversibility toward VO 2+ /VO2 + and V 2+ /V 3+ redox couples is prepared in the conditions of VHNO3 /mpGF =0.45 mL g −1 at 200 °C in 300 min (m-GF-0.45). The nitric acid vapor reaction with graphite felts occurs preferentially on the surface of amorphous carbon and at defect sites in the graphitic structure, yields N2 and carbon-oxygen surface complexes, resulting in a higher double layer capacity (DLC) from 146 μF mg −1 (p-GF) to 1514 μF mg −1 (m-GF-0.45). Thus, the energy efficiency and discharge capacity of m-GF-0.45 electrode increases significantly by 8.7% and 100% at 150 mA cm −2, respectively.